Exposure to tobacco secondhand smoke and its associated factors among non-smoking adults in smoking-restricted and non-restricted areas: Findings from a nationwide study in Malaysia - Lim K.H.; Teh C.H.; Nik Mohamed M.H.; Pan S.; Ling M.Y.; Mohd Yusoff M.F.; Hassan N.; Baharom N.; Dawam N.D.; Ismail N.; Ghazali S.M.; Cheong K.C.; et al. (BMJ Publishing Group, 2024)
Indexed by WOS/SCOPUS/ERA